PTU-067 Body Composition Profiling is a Predictor of Therapeutic Outcome in Patients with Moderate to Severe Crohn's Disease. (17th August 2016) - Ding, NS; Malietzis, G; Lung, PF; Yip, WM; Penez, L; Ganeshanathan, T; Gabe, SM; Jenkins, JT; Hart, AL
Abstract : Introduction: Anti-tumour necrosis factor (TNF)s form a major part of therapy in Crohn's disease and has a primary non-response rate of 10–30% and a secondary loss of response rate of 5% per patient-year. Myopenia is prevalent in patients with Crohn's disease who are in clinical remission and can be measured using body composition analysis tools. We hypothesise that body composition can predict for outcomes of anti-TNF primary non-response and secondary loss of response. Methods: Between January 2007 to June 2012, 650 anti-TNF naïve patients underwent anti-TNF therapy for Crohn's disease in a single centre. CT images were analysed for body composition parameters and used to estimate body fat-free mass. The outcome measures were primary non-response and secondary loss of response. COX-regression analysis was used to predict for outcomes with three-year follow-up data. A hypothetical dose of 5 mg/kg was delivered with estimated tissue levels. Results: Of the 650 patients with anti-TNF therapy, 106 were included. 26 (24.5%) were primary non-responders and 29 (27.4%) had secondary loss of response. 13 patients were obese (BMI > 30). Sex-specific cut-offs that defined a significant association between low muscle, high visceral fat and myosteatosis with outcomes were ascertained by stratification analysis. On multivariate analysis, myopenia predicted for primary non-response (HR 4.74;1.81-12.39, p =0.002) (Figure 1). Large anti-TNF dose variations resulted due to different body compositions. (Figure 2) Conclusion: In this cohort study with three-year follow-up data, body composition profiles varied widely and did not correlate well with BMI. Myopenia was a predictor of primary non-response with potential implications for dosing and serves as an explanation for pharmacokinetic failure. Disclosure of Interest: None Declared